Increasing of size and fastness of adhesive binding in system steel wire cord — rubber, offered by RUP “Belarussian metallurgical works” - S. A. Isakov; V. V. Flippov (Литьë и металлургия)
There are analyzed the existing world directions of the development of new metal cord coverings. The results of the development and mastering of the new way of brass covering in conditions of RUP BMZ allowing to produce the ultrahigh-strength metal cord, are given.